From Policy to Culture: A Narrative Study on Organizational Culture Transformation through Green Human Resource Management - Burhanuddin (Malaqbi Publisher, 2025)
This qualitative narrative study investigates the role of Green Human Resource Management (Green HRM) in driving organizational culture transformation toward sustainability in South Sulawesi, Indonesia. As global environmental challenges intensify, organizations are increasingly tasked with moving beyond policy compliance to embedding ecological consciousness into their cultural fabric. Through semi-structured interviews with HR professionals and employees in two environmentally certified companies, this research explores how Green HRM practices such as green recruitment, eco-training, and sustainability-aligned performance appraisals reshape values, identities, and daily practices. Findings reveal that Green HRM fosters a collective environmental ethos by aligning individual and organizational identities with sustainability goals. Leadership commitment, peer influence, and the integration of ecological metrics into HR systems emerged as critical drivers of cultural change. Participants’ narratives highlighted pride in eco-friendly initiatives and a shift from viewing sustainability as a compliance requirement to a shared responsibility rooted in South Sulawesi’s socio-cultural context, where regional ecological vulnerabilities amplify the urgency of action. However, challenges persist in balancing productivity demands with sustainability imperatives, underscoring the need for adaptive strategies and collaborative problem-solving. This study contributes to the socio-cultural discourse on Green HRM, advocating for context-sensitive approaches that bridge global sustainability agendas with local realities. It offers practical insights for organizations seeking to transform environmental policies into lived cultural values.